MANAJEMEN PESANTREN BERBASIS TAKHASSUS DI PONDOK MODERN DARUL KHOIROT TIRTOYUDO KABUPATEN MALANG - Muhammad Husni; Abd. Rohman (Pascasarjana Institut Agama Islam Al-Qolam, 2023)
The boarding school which is quite comprehensive in management because the curriculum doesn’t only implement Islamic boarding school learning (Kitab Kuning), but also adopts high/high school education. In terms of curriculum management In its implementation in the modern Darul Khoirot boarding school, it integrates boarding school (book) high/high school lessons. Thus, the existence of takhassus-based boarding school management shows the characteristics of Darul Khoirot Tirtoyudo Malang Modern Boarding School which are identical in a particular science. The purpose of this study was to find out how Darul Khoirot Tirtoyudo Islamic Boarding School Malang in the management of Islamic boarding schools based on takhassus. Due to the development of the times, and the coming of problems in education repeatedly, especially for pesantren, if itsn’t managed in such a way, whatever program and curriculum it will be less effective and efficient in its implementation. Keywords: Islamic Boarding School, Takhassus, Management